Gender Based Violence in HIV Testing and Counselling Settings in Kenya – A Human Rights Perspective - Charity Mugure Tongoi (2012)
The main goal of this thesis is to show the various human rights that are being violated in HTC. Another aim is to find out the potential for GBV in the various settings of HTC. This has been done by assessing the settings according to three criteria: the structure of the setting, the safety of the client or counsellor and the assurance of quality and control of services. GBV is usually a consequence of gender order established in a society where hierarchy and power relations characterize the relations between women and men. Therefore, this thesis also investigates on how gender and power relations influence GBV in the HTC. This work was researched through a desk review of literature from books, journals, NGO reports and the internet.